Analisis Sensitivitas Model Linear Programming dalam Optimalisasi Penjualan Produk di Toko Anggrek Plastik - Wakiden, Yuliyani; Wungguli, Djihad; Achmad, Novianita; Abbas, Nurhayati (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
Optimizing sales at plastic orchid shops is an important matter to maximize profit by optimizing to get profit. The linear programming method is one of the operations research techniques to solve optimization problems using linear equations to find the optimal solution by taking into account the constraints which exists. In addition, a sensitivity analysis was carried out to determine the impact parameter changes in the constraints and objectives function that affect changes in production system performance in an effort to gain profits. Based on the linear programming model, the results of profit optimization are obtained Rp.419428,60 with variable values x4 = 60, x7 = 50, x8 = 26,28571. For the sensitivity analysis of the objective function, the values of DeltaC_1, DeltaC2 and DeltaC3 are obtained, it can be seen that the lower limit = 1167 and the upper limit = 4667.193. and for Analysis The sensitivity of the constrain function obtained by the NRK value has seven no constraints active and three active constraints.